Identifying Adverse Drug Events by Relational Learning - Page, David; Santos Costa, Vitor; Natarajan, Sriraam; Barnard, Aubrey; Peissig, Peggy; Caldwell, Michael (Proceedings of the AAAI Conference on Artificial Intelligence, 2021)
The pharmaceutical industry, consumer protection groups, users of medications and government oversight agencies are all strongly interested in identifying adverse reactions to drugs. While a clinical trial of a drug may use only a thousand patients, once a drug is released on the market it may be taken by millions of patients. As a result, in many cases adverse drug events (ADEs) are observed in the broader population that were not identiﬁed during clinical trials. Therefore, there is a need for continued, postmarketing surveillance of drugs to identify previously-unanticipated ADEs. This paper casts this problem as a reverse machine learning task, related to relational subgroup discovery and provides an initial evaluation of this approach based on experiments with an actual EMR/EHR and known adverse drug events.